The effect of endosulfan on behavioral activity on fresh water female crab Brytelphusa guerini. - B, Deshai R; P, Katore B; D, Shinde V; E, Ambore N (International Multidisciplinary Research Journal, 2012)
Behavior includes all those process by which an animal senses the external world and internal state of its body, and responds to changes which it perceives. Many of such processes will take place inside the nervous system and may not be directly observed but reflected through the behavior of the animal. When a toxic compound is administered, some changes occur from the normal behavior, and they can be observed externally. These behavioral changes would be caused by the changes in the nervous system caused directly or through metabolic or physiological activities. The paper deals with toxic effect of endosulfan on fresh water female crab Barytelphusa guerini and its behavioral study. The experimental animal shows various activities which is recorded and discussed.